1995
DOI: 10.1007/bf00337576
|View full text |Cite
|
Sign up to set email alerts
|

Acute obstruction from tumour in the left colon without spread

Abstract: Staged resection (group T) versus acute resection (group R) for cure was compared in a randomized study of 121 patients presenting with signs of leftsided obstructive colorectal tumours during emergency surgery from 1978 to 1993. Patients with distant spread were excluded. Transverse colostomy was done in 58 and resection without immediate anastomosis in 56. Duration of emergency surgery was shorter, blood-transfusions less and wound infections less frequent in T compared to R, but postoperative mortality was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(14 citation statements)
references
References 13 publications
0
12
0
1
Order By: Relevance
“…Its application even increased after the closure of the Dutch Stent-In II trial because of stent related morbidity in 2009. Overall, the mortality rate after acute resection was 6.9%, which is lower than often reported mortality rates between 12 and 35% in literature [4,8,9,10]. However, mortality after emergency surgery was highly variable depending on the presence or absence of certain risk factors.…”
Section: Discussionmentioning
confidence: 40%
“…Its application even increased after the closure of the Dutch Stent-In II trial because of stent related morbidity in 2009. Overall, the mortality rate after acute resection was 6.9%, which is lower than often reported mortality rates between 12 and 35% in literature [4,8,9,10]. However, mortality after emergency surgery was highly variable depending on the presence or absence of certain risk factors.…”
Section: Discussionmentioning
confidence: 40%
“…There is only one RCT study, by Kromborg et al in 1995, comparing emergency colostomy with three stages procedure (58 patients) versus HP (63 patients) for OLCC. The authors showed no difference in terms of mortality (8/58 vs. 8/63 patients) and morbidity rate, recurrence rate and cancer specific survival; the overall length of hospital stay was shorter in the resection group [9]. However this RCT has some important limitations due to methodological flaws: no prior sample size estimation; a 15-year accrual period; procedures being performed by 36 attending and training surgeons; incomplete follow up; heterogeneous underlying pathology (with non-malignant strictures accounting for 14% of cases).…”
Section: Resultsmentioning
confidence: 99%
“…Our literature review reveals that C does not provide any short- or long-term benefit over the HP whereas the multiple operations are associated with longer overall hospital stay: 49 days in group C vs. 35 days in HP group (p = 0.01); finally the staged approach shows a not significant tendency to expose the patient to a higher cumulative morbidity as a result of multiple operations[9]. …”
Section: Resultsmentioning
confidence: 99%
“…Although the optimal treatment for patients with left side obstruction in CRC remains controversial, most studies report better results for staged management [16, 2123]. Kronborg et al [4] demonstrated in the only randomised trial of emergency colostomy versus acute resection in patients with left-sided colonic or rectal obstruction that the only advantage with acute resection was a shorter hospital stay. In the present study, the SEMS group had shorter hospital stay after the initial operation.…”
Section: Discussionmentioning
confidence: 99%